COLLABORATIVE GOVERNANCE BETWEEN LEGAL AID INSTITUTIONS AND THE MINISTRY OF LAW IN PROTECTING THE POOR COMMUNITIES RIGHTS - Grace Kelly Hadi Putri Sihombing; Yunika Depri Listiana; Eka Mustikasari (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study examines how the Legal Aid Institute (LAI) and the Ministry of Law in West Kalimantan Province have partnered to provide legal aid to the underprivileged through collaborative governance. Although access to justice is a human right guaranteed by the Constitution, structural, social, and economic barriers make it difficult for the impoverished actually to obtain it. Even though the state’s duty to provide free legal aid services has been upheld by Law Number 16 of 2011 concerning Legal Aid, program accomplishments at the regional level still reveal a disconnect between goals and actualization. Only 37 of the 87 litigation legal aid cases intended for West Kalimantan Province in 2024 were completed. In-depth interviews, field observations, and document analysis are among the data collection methods used in this descriptive qualitative study. Four legal counsellors from the Ministry of Law’s Regional Office, two managers and advocates from partner LAIs, and recipients of community legal aid were purposively selected as informants. The Legal Aid Database Information System (Sistem Informasi Database Bantuan Hukum/SIDBANKUM) application was used to conduct observations over several weeks on the legal consultation process, investigation support, trial support, and administrative reporting. The Ansell and Gash collaborative governance framework, which highlights the initial conditions of collaboration, institutional Design, facilitative leadership, and collaborative processes such as face-to-face communication, trust-building, commitment to shared goals, and shared accomplishments, was used to analyze the data. The study’s conclusions show that although cooperation between LAI and the Ministry of Law has been formally established through cooperation contracts and accreditation procedures, it has not yet been implemented as effectively as it could. Low trust between actors and a lack of commitment to common objectives have been caused by resource inequality, complicated administrative processes, financial limitations, poor communication, and a lack of cooperative assessment. This study demonstrates that a critical precondition for improving the efficacy and sustainability of equitable legal aid provision is strengthening the relational dimension of collaborative governance through enhanced facilitative leadership, streamlined procedures, and the deliberative involvement of LAI.